Seroprevalence of SARS-CoV-2 virus infection in undergraduate health sciences students from a public university - López Reyes, Lucy (2022)
Introduction. On March 5 2020, the first case of COVID-19 was reported and on March 16, order of quarantine was issued which resulted in interruption of academic activities. Objective. Determine the seroprevalence and risk factors associated to SARS-CoV-2 infection in undergraduate students of the school of medicine in a public university. Methods. Descriptive cross-sectional study by means of a serology survey to a representative sample of the population of undergraduate students of a health sciences school using a rapid test to detect antibodies IgG, IGM or both in a total blood sample by digital punction. Results. On August 2021, 24,92% (IC95% 18,2-33,0) of students of health sciences tested positive for antibodies anti SARS-CoV-2, 21,2% for IgG, 2,3% for IGM and 0,8% for both; 75,08% (IC95% 66,9-82,0) tested negative antibodies. Conclusions. The seroprevalence in students was not different from the seroprevalence in general population. Therefore, in order to restart presential academic activities this population must be vaccinated and other nonpharmacological requirements should be accomplished for prevention and control of the pandemics such as natural ventilation of classrooms, use of personal protection equipment – masks, hand washing and keeping physical distancing.